Short-stories about time in the making of participatory projects - Alpalhão, Luísa (2017)
Five short stories that occurred during the development of different urban interventions, aka participatory projects for the making of shared public spaces, initiated by atelier urban nomads will be described in this paper Each of the five projects share the intention of being catalysts for the social and spatial transformation of neglected urban spaces aiming to enhance the life quality of the inhabitants of those territories, providing alternative modes of social interaction that differ from the proliferation of social media platforms that solely allow interaction in a parallel reality with ambiguous spatial settings. Each story illustrates a different approach to time in the development or delivery of the interventions - time becoming a core element for an understanding of the intentions and outcomes of the urban interventions themselves. Together, all stories intend to challenge the ubiquitous paradigm conferred to participatory projects as supposed means of exerting democratic values and of promoting a fairer way to create our built environment. The different stories will scrutinize some of the complexities ingrained in interventions of this nature: participatory and situated at the intersection between art, activism and urban space.